Workshop Evaluasi Pembelajaran Daring bagi Guru Sekolah Dasar Mitra PGSD UNM Kampus VI Bone - Asriadi Asriadi; Achmad Shabir; Muhammad Farid (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
Online learning during Covid-19 pandemic allows teaching and learning activities to occur without having to meet physically and at a distance by utilizing a computer or smartphone. However, the digital skills of Indonesian teachers are still low. So that the evaluation of online learning outcomes is less effective and does not characterize evaluations that measure cognitive, affective and psychomotor abilities. Evaluation is mostly done by giving assignments via Whatsapp, not measurements or tests. While there are many applications that can be used to measure student learning progress, such as Google Forms, Kahoot, Quizizz, and Wordwall. Therefore, community service was carried out in the form of a Workshop of online learning evaluation for elementary school teachers: partners of PGSD UNM Campus VI Bone. This community service is carried out by means of lectures, demonstrations or practices, and evaluation of the results of the training. The result shows that teachers master the use of Google Forms as an effective evaluation platform. Partner teachers are expected to be able to train colleagues both through workshops at the school level and at the Teacher Working Group to improve the digital skills of Indonesian teachers.